Prevalence of Scapulocostal Syndrome in Healthcare Professionals: Scapulocostal Syndrome in Healthcare Professionals - Fatima, Nida; Saeed, Rabia; Toqueer, Sana; Sukhera, Sadia; Ahmed, Taimoor; Zaidi, Syeda Tanveer (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2025)
Scapulocostal syndrome is a musculoskeletal condition characterized by pain and dysfunction between the scapula and rib cage. It is particularly prevalent among healthcare professionals due to repetitive movements, poor posture, and prolonged static positions during patient care. Objective: To determine the prevalence of scapulocostal syndrome in healthcare professionals. Methods: It was a cross-sectional study design. A sample size of 286 was selected. The Numerical Pain Rating Scale (NPRS) and Pressure Pain Threshold (PPT) are used to assess pain. SPSS version 26.0 was used for data analysis. Functional disability was checked by using the DASH scale. PPT and trigger point palpation were used exclusively for diagnostic confirmation of SCS (per Simons' criteria) and participant eligibility. Results: The study involved 286 participants aged 25 to 45 years, with a majority being female (55.9%). The mean height was 1.69 ± 0.09 m, and the mean weight was 71.27 ± 14.29 kg, with 60.8% classified as overweight. Among affected muscles in scapulocostal syndrome, the rhomboid (22.0%) and serratus posterior superior (21.3%) were most common. 52.1% exhibited forward head posture (ranging from slight to severe), and 51.0% showed scapular position abnormalities. The average cervicovertebral angle was 49.75° ± 5.73°. Participants reported moderate pain levels (4.98 ± 3.24 NPRS) and moderate functional disability, with a mean DASH total score of 52.19 ± 6.70. Conclusions: Scapulocostal syndrome primarily affects the rhomboid and serratus posterior superior muscles. Most participants showed forward head posture, which is linked to pain and reduced function. Moderate pain and disability levels highlight the condition’s impact on physical abilities.